The exploration of corporate image sustainability: A Netnography study - Utama, Anak Agung Gde Satia; Basuki, Basuki (Department of Anthropology, Faculty of Social and Political Sciences, Hasanuddin University., 2023)
This study aims to investigate the corporate image of six significant online organizational communities and their efforts to achieve sustainability. The research focuses on exploring the communication, interaction, and connection strategies employed by these companies on social media platforms to build their corporate image. The study adopts a Netnography approach, employing thematic content analysis, sentiment analysis, and social network analysis to analyze the collected data. The findings of the analysis reveal various patterns in companies' communication approaches on social media, emphasizing their commitment to sustainability. The study also highlights the importance of transparency and collaboration in building a positive corporate image and fostering stakeholder engagement. Overall, the research contributes to the growing body of knowledge on sustainability communication and social media's role in shaping corporate sustainability image.